2008
DOI: 10.1176/appi.ajp.2007.07071110
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Brain Volume Loss Over Time in Cannabis-Using First-Episode Schizophrenia Patients

Abstract: First-episode schizophrenia patients who use cannabis show a more pronounced brain volume reduction over a 5-year follow-up than patients with schizophrenia who do not use cannabis. These results may help explain some of the detrimental effects of cannabis use in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(109 citation statements)
references
References 41 publications
6
97
1
5
Order By: Relevance
“…Our findings support an interpretation of dosedependent neurotoxic effects, broadly across the hippocampus, as evidenced also by animal studies (see Solowij et al, 2012). The combined effects of comorbid chronic cannabis use and schizophrenia appear to exceed those of either condition occurring in isolation, consistent with other recent studies (Habets et al, 2011;Rais et al, 2008;Solowij et al, 2011). Future studies with larger samples could examine further gender effects and the functional, clinical and neuropsychological correlates of this neuropathology.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings support an interpretation of dosedependent neurotoxic effects, broadly across the hippocampus, as evidenced also by animal studies (see Solowij et al, 2012). The combined effects of comorbid chronic cannabis use and schizophrenia appear to exceed those of either condition occurring in isolation, consistent with other recent studies (Habets et al, 2011;Rais et al, 2008;Solowij et al, 2011). Future studies with larger samples could examine further gender effects and the functional, clinical and neuropsychological correlates of this neuropathology.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this hypothesis, cannabis use was found to be associated with reduced hippocampal and amygdala volume in healthy controls (Yücel et al, 2008) and with excessive cortical thinning in patients with a psychotic disorder compared with cannabisusing healthy controls (Habets et al, 2011). In addition, cannabis-using patients with schizophrenia were found to have larger reductions of gray matter volume than nonusing schizophrenia patients (Rais et al, 2008), especially in areas with high expression of cannabinoid type 1 (CB1) receptors (Rais et al, 2010). The relationship between cannabis and cognition in patients with schizophrenia may be more complex, however, as recent meta-analyses found that in patients with schizophrenia, lifetime cannabis use is associated with better rather than worse cognitive performance (Rabin et al, 2011;Yücel et al, 2010).…”
Section: Introductionmentioning
confidence: 70%
“…Die graue Substanz war jedoch nur bei starkem Tabakkonsum (>25 Zigaretten/Tag) signifikant reduziert [82]. Auch exzessiver Alkoholkonsum [83,84] und intensiver Cannabisgebrauch [85,86] können zur Hirnvolumenminderung beitragen. So wurde beobachtet, dass bei Vorhandensein spezifischer Cannabinoid-1-Rezeptor-Genotypen (CB1/CNR1) Cannabis zur Verminderung der weißen Substanz und kognitiven Defiziten führ-te [87].…”
Section: Genetische Effekte Und Auswirkungen Von Tabak Und Cannabisunclassified